2011
DOI: 10.1108/17415651111189469
|View full text |Cite
|
Sign up to set email alerts
|

Enabling user to user interactions in web lectures with history‐aware user awareness

Abstract: Purpose -The purpose of this paper is to present a user interface for web lectures for engaging with other users while working with video based learning content. The application allows its users to ask questions about the content and to get answers from those users that currently online are more familiar with it. The filtering is based on the evaluation of past user interaction data in time-based media. Design/methodology/approach -The work is implemented as a prototype application in the context of the Openca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Literature review revealed that UTAUT has become one of the most embraced and widely used models for testing the adaptation of ICTs in various fields, such as online learning, internet banking, online recruitment process, online ticketing system and e-governance adoption (Farooq, 2016; Nair et al , 2015; Schaupp et al , 2010; Wulff et al , 2014). According to Tosuntaş et al (2015), UTAUT is one of the extensively used models for testing the acceptance and use of various technologies in a number of different studies (Farooq et al , 2016; Ketterl et al , 2011; Nair et al , 2015; Teo, 2011). With its four exogenous constructs, i.e.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 4 more Smart Citations
“…Literature review revealed that UTAUT has become one of the most embraced and widely used models for testing the adaptation of ICTs in various fields, such as online learning, internet banking, online recruitment process, online ticketing system and e-governance adoption (Farooq, 2016; Nair et al , 2015; Schaupp et al , 2010; Wulff et al , 2014). According to Tosuntaş et al (2015), UTAUT is one of the extensively used models for testing the acceptance and use of various technologies in a number of different studies (Farooq et al , 2016; Ketterl et al , 2011; Nair et al , 2015; Teo, 2011). With its four exogenous constructs, i.e.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…As a result of the rapid advancement in technology, the recent few years have seen an extensive growth in the use of different approaches and implications of technology which have created a global impact in the delivery of education (Farooq, 2016). Although it is evident that the incorporation of technological advancements in various educational methods has led to a user-friendly, supportive and flexible learning environment which is a hallmark of today’s educational system in advanced countries (Ketterl et al , 2011). Various scholars (Danielson et al , 2014; Farooq, 2016; Nair et al , 2015; Tatli and Kiliç, 2015) have reported the positive impact of technology integration on students’ learning outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations